The Effect of Transformational Leadership and Work Environment on Teacher Performance, With Organizational Commitment As An Intervening Variable, At SMPN In Cilegon City - Yusuf, Furtasan Ali; Hayadi, B. Herawan; Sumiyati, Sumiyati (CV. Tripe Konsultan, 2024)
Education is essential for human development and the progress of the Indonesian nation in various fields, including science. An effective school principal must view the school as a unique entity and fulfill their leadership role adeptly. Teachers are crucial to education quality, and elements like transformational leadership, work environment, and commitment significantly enhance their performance. Transformational leadership inspires and empowers educators, fostering a supportive work atmosphere that boosts their satisfaction and motivation. High levels of teacher commitment, shown through dedication to educational activities, also improve performance. This study uses a quantitative survey method conducted in State Junior High Schools in Cilegon, with a sample of 85 teachers selected from a population of 546. The findings highlight the importance of effective transformational leadership by principals in enhancing organizational commitment within schools. Furthermore, the significant direct influence of the principal's transformational leadership on teacher performance at SMPN in Cilegon indicates that enhancing the principal's transformational leadership is crucial for improving teacher performance. Lastly, the significant direct effect of the work environment on teacher performance at SMPN in Cilegon further emphasizes the importance of a supportive work environment.